2001
DOI: 10.1046/j.1365-2958.2001.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel deoxynucleoside‐phosphorylating enzymes in mycoplasmas: evidence for efficient utilization of deoxynucleosides

Abstract: SummaryMycoplasmas are unable to synthesize purine and pyrimidine bases de novo. Therefore, salvage of existing nucleosides and bases is essential for their survival. Four mycoplasma species were studied with regard to their ability to phosphorylate deoxynucleosides. High levels of thymidine kinase (TK), deoxycytidine kinase (dCK), deoxyguanosine kinase (dGK) and deoxyadenosine kinase (dAK) activities were detected in extracts from Mycoplasma pneumoniae, Mycoplasma mycoides subsp. mycoides SC (M. mymySC), Acho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 29 publications
1
59
2
Order By: Relevance
“…Mycoplasma species are thought to be completely dependent on their host for supplying these nucleic acid precursors. Genomic sequence analyses of a number of Mycoplasma species have identified novel enzymes associated with salvage pathways for biosynthesis of nucleic acids from nucleotides (41,53,54). Mycoplasma nucleases are thought to play a metabolic role in the production of nucleotide substrates from host or microbial nucleic acids released through natural and induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma species are thought to be completely dependent on their host for supplying these nucleic acid precursors. Genomic sequence analyses of a number of Mycoplasma species have identified novel enzymes associated with salvage pathways for biosynthesis of nucleic acids from nucleotides (41,53,54). Mycoplasma nucleases are thought to play a metabolic role in the production of nucleotide substrates from host or microbial nucleic acids released through natural and induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…mycoides (Rodwell, 1960) and Acholeplasma laidlawii (Rodwell and Mitchell, 1979), which became biochemical research models for Mollicutes (Pollack et al, 1997). These studies revealed the general metabolic capabilities of these organisms and some exciting new findings, such as PPi-dependent nucleoside kinase activities, never described previously in any living organism (Tryon and Pollack, 1984;Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 85%
“…When converting nucleobases into nucleosides, these enzymes can accept a deoxyribose-1-phosphate instead of ribose-1-phosphate, generating deoxyribonucleosides. It was also found that mycoplasmas have the ability to phosphorylate all natural deoxynucleosides via deoxynucleoside kinases with ATP-dependent activities but also, in some species, NMP-dependent (phosphotransferases) and PPi-dependent activities (Wang et al, 2001).…”
Section: Purine and Pyrimidine Nucleotide Pathways In Mollicutesmentioning
confidence: 99%
“…However, genomic sequence analyses of a number of mycoplasma species have identified novel enzymes associated with salvage pathways for the biosynthesis of nucleic acids from nucleotides (5,21,24,34,42,44,51,(57)(58)(59). These salvage pathways have been functionally characterized in Mycoplasma mycoides subspecies mycoides (35)(36)(37)58). Mycoplasma nucleases are thought to play a metabolic role in the production of nucleotide substrates from host or microbial nucleic acids released through natural and induced cell death.…”
mentioning
confidence: 99%